30 Change management theory that is fit for the times and fit for purpose: back to the future with kurt lewin. (31st October 2017) - Martin, K; Colville, I
Abstract : Academic change management theory is relevant in medicine. Clinicians accustomed to using evidence based practice for their patients can benefit from combining it with evidence based management theories. This paper draws on the seminal work of Kurt Lewin, the founding father of academic change management, to show how a deep appreciation of his work enables us to make sense of contemporary times and challenges. This is demonstrated in a context where, following the joint re-commissioning by the CCG, NHS England and council of community Children's Health Services in Wiltshire Virgin Care was commissioned to provide bring together services from five separate providers to create a single service for the county from 1 April 2016.Lewin's theory furnishes a way of mapping the gap between 'where we are' and 'where we want to be' and in so doing produces an analysis/map for a change journey that is not only academically rigorous but also of practical relevance. The field analysis allowed the senior management team to understand the cultures in the different merging organisations, and staff groups so that they could approach the desired changes in a style that allowed increased moving forces rather than strengthening the restraining forces. Driving forward change tends to increase restraining forces but recognising these and modifying communication styles and time frames lessened the restraining forces. At the end of the first year of the contract the first year of the transformation plan has been successfully delivered and there is a strong sense of belonging amongst staff in the new organisation as demonstrated by the staff satisfaction survey at the beginning and end of the year.